2018
DOI: 10.1186/s13065-018-0468-4
|View full text |Cite|
|
Sign up to set email alerts
|

Physicochemical properties of polysaccharides from Dendrobium officinale by fractional precipitation and their preliminary antioxidant and anti-HepG2 cells activities in vitro

Abstract: BackgroundDendrobium officinale as a precious traditional Chinese herb is widely used in medicines and health supplements. Thus the extraction, purification and biological activities of polysaccharides from the stem of Dendrobium officinale have significant meaning on theory and application value.MethodsThe crude Dendrobium officinale polysaccharide (DOP) was obtained by hot water extraction- ethanol precipitation method, and four new polysaccharide fractions (DOP-40, DOP-50, DOP-60, and DOP-70) were further o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 33 publications
(33 reference statements)
1
24
0
Order By: Relevance
“…Accumulating evidence showed that D. officinale polysaccharides exhibited valuable high free radicals scavenging activity (Luo et al 2016;Xing et al 2018). In a recent report, a water-soluble polysaccharide obtained from D. officinale has been proved to possess excellent scavenging activity of hydroxyl radical and 1,1diphenyl-2-picrylhydrazyl (DPPH) (Luo et al 2016).…”
Section: Dop Decreases Free Radicals (Ros)mentioning
confidence: 99%
See 3 more Smart Citations
“…Accumulating evidence showed that D. officinale polysaccharides exhibited valuable high free radicals scavenging activity (Luo et al 2016;Xing et al 2018). In a recent report, a water-soluble polysaccharide obtained from D. officinale has been proved to possess excellent scavenging activity of hydroxyl radical and 1,1diphenyl-2-picrylhydrazyl (DPPH) (Luo et al 2016).…”
Section: Dop Decreases Free Radicals (Ros)mentioning
confidence: 99%
“…In a recent report, a water-soluble polysaccharide obtained from D. officinale has been proved to possess excellent scavenging activity of hydroxyl radical and 1,1diphenyl-2-picrylhydrazyl (DPPH) (Luo et al 2016). Xing et al (2018) adopted the ethanol extract method to obtain four purified fractions of DOP (DOP-40, DOP-50, DOP-60 and DOP-70) and found that DOP-40, DOP-60 and DOP-70 exhibited high scavenging activity of O 2 -, DPPH and hydroxyl radicals. Among them, DOP-70 demonstrated the strongest antioxidant ability.…”
Section: Dop Decreases Free Radicals (Ros)mentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, polysaccharides, bibenzyls, alkaloids, and flavones have been confirmed as the major and bioactive ingredients [ 3 , 4 ]. The abundance of polysaccharides in its stems and the specific alkaloids make D. officinale have anticancer [ 1 ], anti-oxidant [ 5 ], and anti-inflammatory effects [ 1 , 6 ] as well as support immune modulation [ 7 , 8 ], hepatop protection, and hypoglycemia [ 8 , 9 ]. Due to its multiple health benefits, demand for high-quality D. officinale is increasing across medicine, food, and skin care.…”
Section: Introductionmentioning
confidence: 99%